Treatment of pediatric intracranial aneurysms: case series and meta-analysis. (12th August 2018) - Yasin, Junaid T; Wallace, Adam N; Madaelil, Thomas P; Osbun, Joshua W; Moran, Christopher J; Cross, Dewitte T; Limbrick, David D; Zipfel, Gregory J; Dacey, Ralph G; Kansagra, Akash P
Abstract : Background: There are limited outcome data to guide the choice of treatment in pediatric patients with cerebral aneurysms. Objective: To describe our institutional experience treating pediatric patients with cerebral aneurysms and to conduct a meta-analysis of available studies to provide the best current evidence on treatment related outcomes. Methods: We identified pediatric patients with cerebral aneurysms evaluated or treated at our institution using a comprehensive case log. We also identified studies to include in a meta-analysis through a systematic search of Pubmed, SCOPUS, EMBASE, and the Cochrane Database of Systematic Reviews. As part of both the local analysis and meta-analysis, we recorded patient characteristics, aneurysm characteristics, management, and outcomes. Statistical analysis was performed using Fisher's exact test and the two tailed Student's t test, as appropriate. Results: 42 pediatric patients with 57 aneurysms were evaluated at our institution, and treatment specific outcome data were available in 560 patients as part of our meta-analysis. Endovascular and surgical treatments yielded comparable rates of favorable outcome in all children (88.3% vs 82.7%, respectively, P=0.097), in children with ruptured aneurysms (75% vs 83%, respectively, P=0.357), and in children with unruptured aneurysms (96% vs 97%, respectively, P=1.000). Conclusion: Endovascular and surgical treatment yield comparable long term clinical outcomes in pediatric patients with cerebral aneurysms.